Comparative effectiveness of Ginkgo injections for treating vertebrobasilar insufficiency: A systematic review and network meta‐analysis. (19th November 2019) - Cao, Huijuan; Tan, Di; Wang, Kaihuan; Duan, Xiaojiao; Wu, Jiarui; Liu, Xinkui; Ni, Mengwei; Tian, Jinhui; Liu, Shi
Abstract: What is known and objective: This study sought to assess the clinical effectiveness of Ginkgo injections (GIs) combined with conventional drugs for vertebrobasilar insufficiency (VBI). Methods: Randomized controlled trials (RCTs) that assessed the adjunctive effects of GIs for patients with VBI were retrieved from several English and Chinese databases from inception to December 2018. The Cochrane risk of bias method was used to evaluate the methodological quality of the eligible trials. The data were analysed by Stata 13.0 and WinBUGS 1.4.3 software. Results: A total of 20 RCTs that included 1710 patients were included. All RCTs had an unclear risk of bias or a high risk of bias. The network meta‐analysis (NMA) showed that the use of four kinds of GIs, especially Ginkgo leaf extract and dipyridamole injections (GDs), as adjunctive therapies with drugs for VBI increased the total effectiveness rate. Ginkgo biloba leaf extract injections (EGbs) combined with conventional drugs were more effective than only conventional drugs for improving the results of transcranial Doppler ultrasonography (TCD). Shuxuening injections (SXNs) seemed superior for improving blood viscosity‐related indicators. Adverse events were mentioned in nine trials, and there was no difference between the GI group and the control group for the incidence rate of adverse events. What is new and conclusions: GIs showed significant benefits as an add‐on therapy for VBI, as GIs increased the total effectiveness rate and improved the results of TCD examinations. Due to the limited sample size and quality of the included trials, the results of this review still need to be tested in larger, rigorous studies in the future. Abstract : To assess the clinical effectiveness of Ginkgo injections (GIs) combined with conventional drugs for vertebrobasilar insufficiency, we conducted this network meta‐analysis with 20 included trials. Four kinds of GIs, especially Ginkgo leaf extract and dipyridamole injections, showed siginificant benefits as add‐on therapy for the disease.